Structural Examination of Moral Injury and PTSD and Their Associations With Suicidal Behavior Among Combat Veterans - Allison R. Battles; Jeremy Jinkerson; Michelle L. Kelley; Richard A. Mason (The University of Alabama, 2022)
Moral injury and post-traumatic stress disorder are argued to be distinct yet related constructs. However, few studies have evaluated the factors distinguishing moral injury from PTSD. The present study sought to extend the work of Bryan et al. (2018) by differentiating the symptomology of moral injury and PTSD and their associations with suicidal behaviors among combat veterans. The study evaluated data from 129 combat veterans exposed to potentially morally injurious events. Exploratory structural equation modeling evaluated a measurement and structural model. Results revealed a four-factor solution, with the relevant factors being PTSD symptoms, guilt/shame, psychiatric comorbidities, and meaning in life. Guilt/shame and psychiatric comorbidities had significant positive effects on suicidal behaviors. The present findings suggest that combat veterans have a complex, dimensional response to combat trauma and pMIE exposure. These results diverged from previous research to suggest that moral injury symptoms may not constitute a single factor but rather a multifaceted constellation of symptoms. The present study also provided evidence that moral injury symptoms are both unique and overlapping with PTSD symptoms. Suicidal behaviors are a major area of concern among veterans, and the findings here implicate guilt/shame and psychiatric comorbidities as related to these suicidal behaviors.